Mapping the Legacy of Audiovisual Archives. The Sardinian Case - Mereu, Myriam (Unlocking Television Archives in the Digital Era. 16th Media Mutations International Conference, 2026)
This paper explores the challenges and opportunities of conducting research on Sardegna Uno, a local television channel founded in 1982 in Cagliari, Sardinia. Drawing on a multimodal methodology combining archival research and oral history, the study highlights the complexities of reconstructing the history of a broadcaster whose official archives are either inaccessible or non-existent. The research is framed within the broader context of the archival turn in television studies, where archives serve as crucial sites for preserving, recollecting, and reusing cultural memory. The authors examine how Sardegna Uno’s materials ranging from newscasts to commercials were largely lost due to practices such as tape reuse and technological obsolescence, reflecting the fragility of local television heritage. The research is based on two years of work within the ATLas project, involving the collection of administrative documents from institutional archives, private collections, and interviews with former Sardegna Uno staff. These testimonies provided valuable insights into the editorial, political, and cultural dynamics of the broadcaster, especially during the turbulent years of 1987–1989 marked by financial crises and restructuring. This study contributes to understanding the vulnerabilities of regional media archives and the importance of oral history in recovering lost media legacies.